Методика проведення органами доходів і зборів поглибленого аналізу зовнішньоекономічної діяльності суб’єктів господарювання - Туржанський, В. А.; Приходченко, Д. Є.; Жиленко, В. В.; Turzhanskyi, V.; Prykhodchenko, D.; Zhylenko, V. (КНТУ, 2016)
У статті відображена методика проведення органами доходів і зборів аналізу зовнішньоекономічної діяльності суб’єктів господарювання щодо дотримання законодавства з питань державної митної справи. Деталізуються етапи поглибленого аналізу зовнішньоекономічної діяльності суб’єктів господарювання. The article is devoted to developing of methodics of in-depth analysis of foreign business entities to comply with the laws of Ukraine on state customs. This methodic is proposed for use by officials of the State Fiscal Service of Ukraine within its authority. The technique includes methods and tools for analysis of foreign trade operations based on information available to the authorities of income and fees, including previous customs information that can be obtained from the customs of other countries.
Мethodics of depth analysis of foreign business entities by revenue and duties authorities
Keywords: зовнішньоекономічна діяльність; методика; аналіз; митний ризик; митні правопорушення; попередня митна інформація; foreign trade; methodology; analysis; risk customs; customs offenses; preliminary customs information